2003
DOI: 10.1161/01.atv.0000066684.37829.16
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H Oxidase Mediates Angiotensin II–Induced Vascular Macrophage Infiltration and Medial Hypertrophy

Abstract: Objective-Our preliminary data suggested that angiotensin II (Ang II)-induced reactive oxygen species are involved in intercellular adhesion molecule-1 (ICAM-1) expression and leukocyte infiltration in the rat thoracic aorta. Other reports demonstrating reactive oxygen species-induced cell growth suggested a potential role of NAD(P)H oxidase in vascular hypertrophy. In the present study, we postulate that NAD(P)H oxidase is functionally involved in Ang II-induced ICAM-1 expression, macrophage infiltration, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 72 publications
7
139
1
3
Order By: Relevance
“…This is consistent with an earlier study that showed that hyperglycemia itself enhances oxidative stress. 39 Oxidative stress, which is also activated by an AT 1 R-mediated pathway 40,41 and promotes myocardial fibrosis, 15,42 is likely to be involved in the development of myocardial fibrosis in DM, as shown in this study. Furthermore, we were able to show that there was a positive correlation between the extent of cardiac ACE expression and that of diastolic dysfunction.…”
Section: Impact Of Dm On Diastolic Dysfunction Myocardial Fibrosis Asupporting
confidence: 60%
“…This is consistent with an earlier study that showed that hyperglycemia itself enhances oxidative stress. 39 Oxidative stress, which is also activated by an AT 1 R-mediated pathway 40,41 and promotes myocardial fibrosis, 15,42 is likely to be involved in the development of myocardial fibrosis in DM, as shown in this study. Furthermore, we were able to show that there was a positive correlation between the extent of cardiac ACE expression and that of diastolic dysfunction.…”
Section: Impact Of Dm On Diastolic Dysfunction Myocardial Fibrosis Asupporting
confidence: 60%
“…5,6 Moreover, AngII given exogenously to rodents has been shown to result in cellular changes within the myocardium, hypertrophy and eventual fibrosis, similar to that seen in humans. 5,[7][8][9] Taken together, this evidence strongly supports a role for AngII in the development of myocardial fibrosis. The direct mechanisms responsible, and the effector cells involved, have yet to be fully characterized.…”
supporting
confidence: 68%
“…This may be due to the difference in the animal model (DSS rat is a low-renin hypertension model). Another study showed a similar result, in which the BP was not affected by gp91ds-tat (190). This has been attributed to the use of 10-fold lower dilution of gp91ds-tat than that used in the original study by Rey et al (270).…”
Section: Phycobilinsmentioning
confidence: 65%